Multiple requirements for nematode spliced leader RNP function in trans-splicing. - Denker, J A (1996)
The 5' exon donor in nematode trans-splicing, the SL RNA, is a small (approximately 100 nt) RNA that resembles cis-spliceosomal U snRNAs. Extensive analyses of the RNA sequence requirements for SL RNA function have revealed four essential elements, the core Sm binding site, three nucleotides immediately downstream of this site, a region of Stem-loop II, and a 5' splice site. Although these elements are necessary and sufficient for SL RNA function in vitro, their respective roles in promoting SL RNA activity have not been elucidated. Furthermore, although it has been shown that assembly of the SL RNA into an Sm RNP is a prerequisite for function, the protein composition of the SL RNP has not been determined. Here, we have used oligoribonucleotide affinity to purify the SL RNP and find that it contains core Sm proteins as well as four specific proteins (175, 40, 30, and 28 kDa). Using in vitro assembly assays; we show that association of the 175- and 30-kDa SL-specific proteins correlates with SL RNP function in trans-splicing. Binding of these proteins depends upon the sequence of the core Sm binding site; SL RNAs containing the U1 snRNA Sm binding site assemble into Sm RNPs that contain core, but not SL-specific proteins. Furthermore, mutational and thiophosphate interference approaches reveal that both the primary nucleotide sequence and a specific phosphate oxygen within a segment of Stemloop II of the SL RNA are required for function. Finally, mutational activation of an unusual cryptic 5' splice site within the SL sequence itself suggests that U5 snRNA may play a primary role in selecting and specifying the 5' splice site in SL addition trans-splicing.